Axial crash performance of press-formed open and end-capped cylindrical tubes – A comparative analysis. (March 2018) - Praveen Kumar, A.; Mohamed, M. Nalla; Jusuf, A.; Dirgantara, T.; Gunawan, L.
Abstract: Thin-walled cylindrical tubes are usually employed as impact energy absorbing members in automotive vehicles due to their high energy absorption capacity through progressive plastic deformation. Despite their superior impact performance, high initial peak force is the crucial problem which has potential to cause serious injury to the occupants. Hence in this study, end-capped cylindrical tubes with reduced initial peak force are proposed as energy absorbing members when subjected to axial static and impact loading conditions. The proposed tubes were fabricated by a multi-stage deep drawing process, that induces forming effects such as thickness variation, and residual stress/strain. Subsequently, numerical simulations were carried out using HyperForm 14.0® and LS-DYNA R-971® with particular attention for the transfer of forming history from deep-drawing simulations to the subsequent crash models. The axial crash performance of the end-capped tubes was also compared with open cylindrical tubes and it was found that the initial peak force of the end-capped tube is significantly reduced by 15–30% than the open cylindrical tube without compromising the energy absorption capacity. The results revealed that end-capped tubes can stabilize the deformation behavior and could be used as a good alternative to the conventional energy absorbing structures in aerospace and automotive applications respectively. Graphical abstract: Highlights: Axial deformation behavior of press-formed open and end-capped cylindrical tubes were investigated. Influence of forming parameters on the crash performance of the tubes was examined through multistage deep-drawing simulation. The initial peak force of the end-capped tube is significantly reduced by 15-30% than the open tube. The initial peak force can be controlled by varying the fillet radius of the end-capped tube.